A comparative study of intracervical foley’s catheter with oxytocin and vaginal misoprostol for induction of labour - ., Priyanka; Arya, Shashi Bala; Sinha, Mirdu; Goel, J. K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Induction of labour implies stimulation of uterine contraction before spontaneous onset of labour with or without ruptured membranes. Aim of this study was to compare the efficacy and safety of intracervical Foley’s catheter with oxytocin and vaginal misoprostol for labour induction at term. Methods: A total 100 term pregnant women were chosen with bishop score <6 and divided into two groups: Foley’s catheter with oxytocin (Group A) and vaginal misoprostol (Group B). In Group A, a 16 F Foley’s catheter introduced beyond internal os and traction applied every 4 hourly to check for expulsion with simultaneous oxytocin infusion (2 mU/min up to 32 mU/min). In Group B, 25 mcg misoprostol administered every 4 hourly (maximum 6 doses or 150 mcg). Data analysed using SPSS software 20.0. A p value <0.05 was considered statistically significant. Results: No statistical difference found between demographic variables between two groups. Both primigravida and multigravida had poor pre-induction bishop score in both groups. Foley’s catheter (80%) and misoprostol group (96%) had successful induction and was statistically significant (p<0.05). Foley’s catheter took more time from induction-delivery both in primigravida and post-dated pregnant women. The rate of cesarean in Foley’s catheter group was high (62.5%) including 33% cases with failed induction. Foley’s catheter had less maternal and neonatal complications, less NICU admission as compared to misoprostol (p>0.05). Conclusions: Misoprostol was found better for successful induction, decreases induction-to-delivery interval and increases vaginal delivery as compared to Foley’s catheter but it needs constant supervision in view of hyperstimulation and tachysystole.